RELATIONSHIP OF SMOKING HABITS AND COFFEE CONSUMPTION WITH TEETH DISCOLORATION IN ALALAK BANJARMASIN - Rosihan Adhani; Rizqi Risfiana Putri; Melisa Budipramana (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Teeth discoloration is a problem in dental practice, among others, the occurrence of teeth discoloration in coffee consumers as much as 77.13%, smokers who experience discoloration 76.7%. Based on data from Riskesdas South Kalimantan in 2018, the prevalence of daily smokers in Banjarmasin City is 18.02%. The highest smoking prevalence is in the population aged 30-34 years, which is 30.01%. Teeth discoloration is affected by extrinsic stains through the deposition of chromogenic materials on the teeth surface such as tobacco, tea and coffee. Teeth discoloration can cause discomfort when speaking, smiling and lack of confidence. Purpose: To analyze the relationship between smoking habits and coffee consumption with teeth discoloration in people aged 30-34 years in Alalak Tengah Village. Method: This research is an analytic observational with a cross sectional approach. The sampling technique used is probability sampling technique with a sample size of 87 people. Result: there was a significant relationship between the number of cigarettes and teeth discoloration 0.018 (p<0.05), the relationship between smoking duration and teeth discoloration was 0.006 (p<0.05), a significant relationship between the type of cigarette and teeth discoloration was 0.002 (p<0.05) and vice versa. There is no significant relationship between coffee consumption and duration of drinking coffee with teeth discoloration. Conclusion: Based on the research, there is a relationship between smoking habit and teeth discoloration. Keywords: Cigarettes, Coffee, Teeth Discoloration.